A Non-PCM-Based 2 × 2 MIMO Antenna Array With Low Radar Cross-Section Using Characteristic Mode Analysis - Manzoor Elahi; Slawomir Koziel; Leifur Leifsson (IEEE Access)
In this paper, we introduced a $2 × 2$ multiple-input-multiple-output (MIMO) antenna array using a non-polarization conversion metasurface (NPCM) with reduced radar cross section (RCS). To achieve a low RCS, a chess-board configuration is typically adopted. However, in conventional NPCM designs, subarrays with 180° phase shifts apart exhibit radiating modes at different resonance frequencies due to varied unit cell sizes and spacing. To address this, a characteristic mode analysis (CMA) has been performed to investigate the radiation mechanism of each subarray, ensuring they resonate within the same frequency band. Through this analysis, the feeding structure was optimized based on the slot-coupled patch antenna theory to align the radiating modes of the subarrays within the desired bandwidth. Specifically, the fundamental mode TM01 of one subarray and higher order mode TM03 of the other were successfully excited to operate within the same frequency range. This configuration enables the low-RCS NPCM surface to implement a MIMO system in which each subarray radiates independently within the same frequency band. Full-wave simulations and measurements have been carried out to verify the performance of the proposed antenna array. The results indicate that the MIMO antenna maintains good isolation, ranging from 22 to 50 dB among ports within the operating band from 9.6 to 10.7 GHz, and exhibits RCS reduction under different polarization ranging from 9 to 19 dB across the band from 8.5 to 12 GHz. Moreover, the RCS under oblique incidence also demonstrate good performance, making it suitable for radar applications.